2017
DOI: 10.1038/s41598-017-08792-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of non-thermal atmospheric plasma on triple-negative breast normal and carcinoma cells through different cell signaling pathways

Abstract: Non-thermal atmospheric plasma (NTP) has shown its selective anticancer effects in many types of tumors in vitro and one of the main mechanisms is that the different increase of intracellular ROS in cancer and homologous normal cells. In this study, we report that NTP treatment reduces the proliferation in triple negative breast cancer (TNBC) and normal cell lines. Simultaneously, STAT3 pathway is inhibited by NTP effects. However, it is observed that normal cells MCF10A are more sensitive to ROS toxicity indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 66 publications
2
45
0
Order By: Relevance
“…The length and diameter of the needles are 2 cm and 1 mm respectively. Similar types of configuration are also reported by other articles [27][28][29][30][31]. In this study, the six fine needles were driven by a high voltage DC and the bacterial suspension served as the ground electrode.…”
Section: Atmospheric-pressure Air Plasmasupporting
confidence: 79%
“…The length and diameter of the needles are 2 cm and 1 mm respectively. Similar types of configuration are also reported by other articles [27][28][29][30][31]. In this study, the six fine needles were driven by a high voltage DC and the bacterial suspension served as the ground electrode.…”
Section: Atmospheric-pressure Air Plasmasupporting
confidence: 79%
“…Consistent with the findings regarding to oxidative stress correlation to cell death with AgNP and CAP continuously mounts the evidence to show that generation of ROS is highly related to the mechanism of AgNP and CAP with the results in current study showed that the cytotoxicity induced by AgNP alone, as well as the combinational treatment AgNP-CAP were efficiently prevented prior NAC treatment up to 10-fold (see Figure 3). The results determine that oxidative stress is responsible for the cytotoxicity of AgNPs and CAP, which is compliant with previous studies portraying the protective effect of NAC when treated with either AgNP or CAP resulting to recovery of proliferative cells [52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
“…Combined CAP-TMZ treatment causes a reduction in cell viability compared to TMZ. The anti-tumor effect of CAP as a standalone therapy in the treatment of glioblastoma and other cancers has been previously investigated [22][23][24][25][26][27][28][29][30] . Positive treatment outcomes reported by several studies make CAP a promising treatment strategy to be evaluated for enhancing sensitivity to TMZ in glioblastoma.…”
Section: Resultsmentioning
confidence: 99%